Simple BODIPY dyes as suitable electron-donors for organic bulk heterojunction photovoltaic cells. (January 2020) - Aguiar, António; Farinhas, Joana; da Silva, Wanderson; Susano, Maria; Silva, Manuela Ramos; Alcácer, Luís; Kumar, Santosh; Brett, Christopher M.A.; Morgado, Jorge; Sobral, Abílio J.F.N.
Abstract: In this work we present the synthesis and characterization (including the report of two new crystal structures) of a series of meso -substituted boron-dipyrromethene (BODIPY) molecules. With an accessible synthesis, these simple BODIPYs have characteristics that par with those BODIPY's having more complex structures, what makes them very interesting materials for industrial production. The photovoltaic performance of the synthesized BODIPY's was evaluated in bulk heterojunction organic solar cells, where they were used as electron-donors. We found that the presence of electron-withdrawing groups has a detrimental effect on the photovoltaic performance, while the meso -free structure shows an improved efficiency in comparison with the meso -substituted BODIPYs. We also studied the origin of the meso -unsubstituted derivative, elucidating at least one of its formation processes, which can open a new way of BODIPY synthesis. Graphical abstract: Image 1 Highlights: Synthesis and characterization of BODIPYs. Explanation of the origin of the meso -free-BODIPY by-product. Performance evaluation of the BODIPY dyes as electron-donors in organic photovoltaic cells.